Sustainable Development Values Inclusion Degree in The Social Studies Curriculum in The First Cycle of Primary Education Stage From The Teacher's and Educational Superintendent's Point of View - ياسين, أحلام; ديوب, وائل; محرز, نورا (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The aim of this research is to recognize the sustainable development values inclusion degree in The First Cycle from the point of view of teacher’s and Educational superintendent’s, And the effect of some variables on it, and In order to achieve the objectives of the research the descriptive analytical method was used and The researcher designed a questionnaire consisting of (41) value distributed over the three dimensions of sustainable development (environmental, social, economic) as for The research sample it consisted of (353) teachers and (35) Educational superintendents in the first cycle schools in Latakia city. and some of the most important search results were : -The availability’s degree of the sustainable development dimensions related values in the curriculums of social studies was moderate, with the environmental dimension in the first place, the social dimension in second, and the economic dimension in the third place. - A statistically significant difference exists between the mean scores of the Research sample units' responses regarding the degree to which the social studies curriculums include the values of sustainable development according to the job title variable (Educational superintendents, teachers). For the benefit of Educational superintendents. -There are no statistically significant differences between the mean scores of the Research sample units' responses regarding the degree to which the social studies curriculums include the values of sustainable development according to the educational qualification and the number of years of experience variables. -A statistically significant difference exists between the mean scores of the Research sample units' responses regarding the degree to which the social studies curriculums include the values of sustainable development according to the variable of the training courses on the developed curriculums. For the followers of one or more training courses.